Isolated splenic Mycobacterium tuberculosis complex infection in an immunocompetent individual with FDG-PET positive mass. Issue 2 (February 2021) - Nishina, Sayaka; Sakai, Hitoshi; Kawakami, Toru; Kanai, Shinichiro; Ushiki, Atsuhito; Natori, Tatsuya; Igarashi, Yuriko; Mitarai, Satoshi; Yoshiyama, Takashi; Ishida, Fumihiro; Nakazawa, Hideyuki
Abstract: Tuberculosis, caused by Mycobacterium tuberculosis complex, is a leading cause of mortality in the world, and 15% of the patients may present with extrapulmonary diseases, including splenic lesion. However, isolated splenic infection with M. tuberculosis complex is very rare. A 19-year-old otherwise healthy woman presented with left flank pain, revealing FDG-avid nodules in the spleen. She did not have pulmonary lesions. Histopathology of splenectomized sample showed granuloma, and subsequent PCR revealed amplification of IS 6110, a genetic sequence exclusively detected in M. tuberculosis complex. A wide range of differential diagnosis of isolated splenic lesion should include M. tuberculosis infection regardless of pulmonary involvement. An elective splenectomy may be mandatory in timely manner.